THE ROLE OF ORGANIZATIONAL CULTURE AND MOTIVATION IN MEDIATING LEADERSHIP STYLE RELATIONSHIPS TO EMPLOYEE PERFORMANCE - Bernath Pardede, Rio; Satriawan, Bambang; Indrayani, Indrayani; Wisbisono, Chablullah (RADJA PUBLIKA, 2022)
This study aims to see the influence of leadership style on the performance of employees in the Department of Environment and Forestry of Riau Islands Province by mediated by organizational culture and motivation. This study is a quantitative study that uses a sample of 63 respondents. Data analysis in this study uses Structural Equation Modeling (SEM) analysis to confirm the dimensions of the concept created and measure how much influence independent variables have on dependent variables. The results showed that: (1) Leadership Style has a positive and significant effect on organizational culture, (2) Leadership Style has a positive and significant effect on employee work motivation, (3) Leadership style has a positive and significant effect on employee performance, (4) Culture does not have a positive and significant effect on employee performance, (5) Motivation positively and significantly affects employee performance, (6) Leadership style affects performance mediated by organizational culture, (7) Leadership style influences performance mediated by work motivation, (8) Organizational culture has a positive and significant effect on work motivation.